β-Thalassemia pathogenic variants in a cohort of children from the East African coast - Macharia, AW; Mochamah, G; Uyoga, S; Ndila, CM; Nyutu, G; Tendwa, M; Nyatichi, E; Makale, J; Ware, RE; Williams, TN (Wiley, 2020)
Background β-Thalassemia is rare in sub-Saharan Africa. Previous studies have suggested that it is limited to specific parts of West Africa. Based on hemoglobin A2 (HbA2) concentrations measured by HPLC, we recently speculated that β-thalassemia might also be present on the East African coast of Kenya. Here, we follow this up using molecular methods. Methods We used raised hemoglobin A2 (HbA2) values (> 4.0% of total Hb) to target all HbAA members of a cohort study in Kilifi, Kenya, for HBB sequencing for β-thalassemia (n = 99) together with a sample of HbAA subjects with lower HbA2 levels. Because HbA2 values are artifactually raised in subjects carrying sickle hemoglobin (HbS) we sequenced all participants with an HPLC pattern showing HbS without HbA (n = 116) and a sample with a pattern showing both HbA and HbS. Results Overall, we identified 83 carriers of four separate β-thalassemia pathogenic variants: three β0-thalassemia [CD22 (GAA→TAA), initiation codon (ATG→ACG), and IVS1-3ʹ end del 25bp] and one β+-thalassemia pathogenic variants (IVS-I-110 (G→A)). We estimated the minimum allele frequency of all variants combined within the study population at 0.3%. Conclusions β-Thalassemia is present in Kilifi, Kenya, an observation that has implications for the diagnosis and clinical care of children from the East Africa region.